2020
DOI: 10.1016/j.phro.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beam quality on reference dosimetry correction factors in magnetic resonance guided radiation therapy

Abstract: Correction factors for reference dosimetry in magnetic resonance (MR) imaging-guided radiation therapy (k) are often determined in setups that combine a conventional 6 MV linac with an electromagnet. This study investigated whether results based on these measurements were applicable for a 7 MV MR-linac using Monte Carlo simulations. For a Farmer-type ionization chamber, k B → ,M,Q was assessed for different tissuephantom ratios (TPR 20,10 ). k B → ,M,Q differed by 0.0029(43) between TPR 20,10 = 0.6790(23)(6 MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The consistency of TPR 20,10 between G0 and G90 lends credence to measuring these factors from G0. This is in agreement with previous Monte Carlo simulations [31] which suggested that a larger TPR 20,10 change of 0.679 (6 MV linac) to 0.703 ( 7MV MRL) did not in uence for the PTW 30013 Farmer by more than 0.5 %.…”
Section: Discussionsupporting
confidence: 93%
“…The consistency of TPR 20,10 between G0 and G90 lends credence to measuring these factors from G0. This is in agreement with previous Monte Carlo simulations [31] which suggested that a larger TPR 20,10 change of 0.679 (6 MV linac) to 0.703 ( 7MV MRL) did not in uence for the PTW 30013 Farmer by more than 0.5 %.…”
Section: Discussionsupporting
confidence: 93%
“…Ideally, reference dosimetry should be performed directly at isocentre from G90 and should this be achievable at 5.0 cm depth, with future vendor-designed 1D tanks, the corresponding factors should be correctly determined [21] and applied. The consistency of TPR 20,10 between G0 and G90 supports measuring these factors from G0, in agreement with previous Monte Carlo simulations [18].…”
Section: Discussionsupporting
confidence: 90%
“…With beam quality dependent factors for reference output, a determination of this angular dependence, or at minimum an assessment of the change in these factors with beam quality, should be evaluated. Previous Monte Carlo simulations [ 18 ] have suggested that a TPR 20,10 change of 0.679 (6 MV linac) to 0.703 (7 MV MRL) did not influence beam quality dependent factors for the PTW 30013 Farmer by more than 0.5%; however, it was felt that confirmation with measurement was warranted.…”
Section: Methodsmentioning
confidence: 99%
“…The correction for the magnetic field, , has a vector component over the B field due to the correction factor having a dependence on the configuration of the photon beam, magnetic field and chamber as described in the " Configuration of chamber long axis, radiation beam central axis and primary magnetic field " section. The correction factor is also dependent on beam quality [ 62 , 70 ]. corrects the measured charge in the magnetic field, , which is set up in the configuration specified by the correction factor.…”
Section: Reference Dosimetrymentioning
confidence: 99%
“…The correction factors presented are for the beam qualities of the MRIdian and Unity respectively. A Monte Carlo study showed a change in of less than 0.5% between beam qualities of values of 0.6790 (6 MV Linac) and 0.7028 (7 MV MRI-linac) [ 70 ]. From this it can be concluded that the change in is small within the beam quality variability of the systems.…”
Section: Reference Dosimetrymentioning
confidence: 99%